HUBUNGAN PEMBERIAN ASI EKSKLUSIF DAN KETEPATAN PEMBERIAN MP-ASI TERHADAP KEJADIAN STUNTING PADA BALITA USIA 6-23 BULAN DI KECAMATAN BANSARI KABUPATEN TEMANGGUNG - Lukito, Diewindya Aulia; Setyaningsih, Aryanti (Jurusan Gizi Poltekkes Kemenkes Bandung, 2023)
Exclusive breastfeeding provides a protective effect by improving the nutritional status of toddlers. Inadequate complementary foods can lead to malnutrition and cause developmental delays and decreased body immunity. The research aimed to determine the relationship between exclusive breastfeeding and the accuracy of giving complementary feeding (MP-ASI) to the incidence of stunting in toddlers aged 6-23 months in Bansari District. The research design used was analytical observational with a cross-sectional approach. The research was conducted in Bansari District with a sample of 85 toddlers in June 2023. The independent variables used were exclusive breastfeeding and complementary feeding while the dependent variable was stunting. Data collection were done using observations, questionnaires, and anthropometric measurements. The instruments used were characteristic questionnaires, exclusive breastfeeding, complementary feeding, and recall forms. Data analysis used Chi-Square (α = 0.05). The prevalence of stunting in toddlers aged 6-23 months in Bansari District is 25.9%. There are 37.6% of toddlers in Bansari District who do not receive exclusive breastfeeding. 62.4% of toddlers in Bansari District were given complementary feeding incorrectly. The results of the analysis test showed no relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 6-23 months in Bansari District (p = 0.518) and there was no relationship between the accuracy of giving complementary feeding and the incidence of stunting in toddlers aged 6-23 months in Bansari District ( p = 0.718). There is no relationship between exclusive breastfeeding and the incidence of stunting in toddlers aged 6-23 months in Bansari District and there is no relationship between the accuracy of complementary feeding and the incidence of stunting in toddlers aged 6-23 months in Bansari District.